Moral Philosophy in Ibn Miskawaih's Thought and Its Relevance to the Digital Moral Crisis - Siregar, Hamdan (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2026)
The rapid advancement of Society 5.0 has created a digital paradox: technological connectivity has increased, yet moral degradation manifested in cyberbullying, hoaxes, and digital hedonism (flexing) has escalated. Existing legal regulations are often insufficient to address the root causes of these behaviors, which lie in the spiritual and psychological realms. This study aims to explore the relevance of Ibnu Miskawaih's moral philosophy as a fundamental solution to the modern digital moral crisis. This research employs a qualitative method with a library research design, utilizing a hermeneutic approach adapted from the